Carbon storage in Sichuan Province (Southwest China) from 1980 to 2050: Spatial-temporal variation, driving factors and future trends - Qinglian Deng; Yuqi Guan; Xiong Duan; Bin Chen; Kun Zeng (PLoS ONE, 2026)
Research on carbon storage is crucial for guiding regional sustainable development. However, Sichuan Province lacks long-term systematic analyses of carbon storage, and the driving mechanisms behind its changes remain unclear. This study systematically examines the spatiotemporal evolution of LUCC(land use/cover change) and carbon storage in Sichuan from 1980 to 2020, analyzes driving factors of carbon storage changes, and simulates future carbon storage distribution under different scenarios, based on LUCC data and 13 driving factors. Key findings include: (1) Over the 40-year period, land use was dominated by grassland, forest land, and farmland, maintaining a stable “grassland/forest land in the west, farmland in the east” pattern, with notable farmland and water body shrinkage alongside grassland and construction land expansion. (2) Total carbon storage showed minor fluctuations (9,201.53–9,209.52 Tg) but exhibited significant spatial heterogeneity, persistently displaying a “high in the west and low in the east” distribution. Water body-to-grassland and farmland-to-forest land conversions substantially increased carbon storage, while forest land-to-grassland and farmland-to-construction land transitions decreased it. (3) Spatial autocorrelation analysis revealed a negative correlation between carbon storage and land use intensity, with pronounced spatial clustering—High-High clusters concentrated in western regions and Low-Low clusters distributed peripherally. (4) Temperature and Digital Elevation Model emerged as dominant factors, while transportation accessibility and precipitation showed minimal influence. Human activities demonstrated moderate regulatory effects, with factor interactions significantly enhancing explanatory power, indicating multi-factor driven changes. (5) Multi-scenario projections (2030–2050) maintained the “high in the west and low in the east” pattern. Compared to 2020, SSP1–1.9 (Shared Socioeconomic Pathway 1–1.9) showed minimal change (10,711.94 ~ 10,712.16 Tg), SSP2–4.5 (Shared Socioeconomic Pathway 2–4.5) exhibited the largest decline (9,243.73 ~ 9,202.01 Tg), and SSP5–8.5 (Shared Socioeconomic Pathway 5–8.5) also decreased notably (9,015.01 ~ 8,980.07 Tg). This study provides a scientific basis for future land use optimization and carbon sink management in Sichuan Province.